Polymer-coated non-toxic stable perovskite quantum dot film and preparation method thereof
Through spin-coating annealing method coated with polymer polymer, a stable copper-based perovskite quantum dot film was prepared in an air environment, solving the problem of difficulty in preparing high-quality and stable quantum dots in the prior art, and achieving excellent optical properties and long-term stability of the material.
Patent Information
- Application Number
- CN202510082669.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-05-02
AI Technical Summary
The prior art is difficult to prepare high-quality and stable copper-based perovskite quantum dot films in air environments, and the stability of the quantum dots is poor and difficult to store for a long time.
A copper-based perovskite quantum dot film is prepared in an air environment by spin-coated annealing method coated with polymers (PMMA, PAN, PVDC). The nucleation size of quantum dots is controlled by domain-limited growth to improve its stability.
It has achieved efficient preparation of stable copper-based perovskite quantum dot films in air environments, which has improved the optical performance and stability of the material and broadened its application prospects in the field of optoelectronics.
Smart Images

Figure CN119912716A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a polymer-coated non-toxic stable perovskite quantum dot film and a preparation method thereof, belonging to the technical field of quantum dot preparation. Background Art
[0002] Perovskite materials have attracted much attention due to their excellent optical properties. Their excellent material properties, such as compositionally tunable emission spectra throughout the visible spectrum, extremely high photoluminescence quantum yield, very narrow emission line width and short exciton radiation lifetime, have attracted widespread attention in modern optoelectronic applications such as solar cells, photodetectors and light-emitting devices.
[0003] In recent years, the emergence of metal halide ABX3-type perovskite materials has further enhanced people's understanding of the solution method for preparing semiconductor nanocrystals or quantum dot materials. This type of material has excellent optoelectronic properties and has great application potential. However, the valence metal Pb in pure inorganic perovskites (such as CsPbBr3) 2+ It has certain toxicity and there are many inconveniences in preparation and recycling, such as the toxicity of the metal lead and its unfriendly nature to the environment. This issue has become a hot topic in the materials industry.
[0004] Harmless Cu has gradually revealed its unique advantages in the field of perovskites, with the advantages of excellent luminescence performance, large Stokes shift, non-toxicity and low cost. Recently, Li et al. proposed a method for preparing pure inorganic Cu-based perovskite halide Cs3Cu2X5 (X=I, Cl, Br). However, this type of quantum dots is generally prepared by ligand-assisted reprecipitation (anti-solvent method), which is very difficult to prepare in an air environment. This is mainly due to the influence of oxygen on the material and the large size of the material grown by the anti-solvent method, which makes it impossible to form quantum dots. At the same time, the stability of quantum dots is poor and it is difficult to preserve them for a long time. At present, how to prepare non-toxic copper-based perovskite quantum dots in an air environment and preserve them for a long time is still a huge challenge. Summary of the invention
[0005] The polymer coating strategy reported in the field of perovskites is mainly applied to lead-based perovskite quantum dots (APbX3, A + =PEA + 、MA + , Cs + etc.;X - =I - , Cl - Br -), however, it is understood that there are no reports on the synthesis and coating strategies of lead-free perovskite quantum dots. In order to solve the problem that it is difficult to prepare good, high-quality and stable quantum dot films in the air environment in the existing technology of copper-based perovskite quantum preparation, this application proposes a technical solution for copper-based perovskite quantum films of quantum dots. On the basis of using high molecular polymers (PMMA, PAN, PVDC) for coating, a method for synthesizing lead-free perovskite quantum dots (CsCu2I3, Cs3Cu2I5, Cs3Cu2Cl5) in an air environment is designed. The use of polymer coating results in confined growth of quantum dots, controls the nucleation size of quantum dots, and uses and optimizes the spin coating process of quantum dot coating. This material has excellent optical properties and stability, and has broad application prospects in the optoelectronic field.
[0006] This application adopts the following technical solutions: According to the first aspect of the present application, a method for preparing a polymer-coated non-toxic and stable perovskite quantum dot film is provided, characterized in that it comprises the following steps: S1. Obtain a raw material containing cuprous halide and cesium halide, add it into DMSO, and stir until it becomes clear and transparent to obtain a precursor solution; S2, obtaining a polymer solution containing a high molecular weight polymer and DMSO; S3, in an air environment, coating the precursor solution and the polymer solution on a carrier once or step by step to obtain a coated carrier, annealing the coated carrier to obtain a non-toxic and stable perovskite quantum dot film coated with the polymer; Wherein, the one-time coating includes mixing the precursor solution and the polymer solution and coating the mixture on the carrier to form a film; The step-by-step coating includes coating the polymer solution on a carrier to form a polymer film, and coating a precursor solution on the polymer film to form a film.
[0007] Optionally, in step S1, the cuprous halide is selected from at least one of CuI and CuCl.
[0008] Optionally, in step S1, the cesium halide is selected from at least one of CsI and CsCl.
[0009] Optionally, in step S1, the usage ratio of the cuprous halide, cesium halide and DMSO is: 1 g: 0.55-0.75 g: 2-4 mL.
[0010] Optionally, in step S2, the high molecular polymer is selected from at least one of methyl methacrylate (PMMA), polyacrylonitrile (PAN), and polyvinylidene chloride (PVDC).
[0011] Optionally, in step S2, the usage ratio of the high molecular weight polymer to DMSO is 1 g: 4-10 mL.
[0012] Optionally, in step S3, in the process of mixing the precursor solution and the polymer solution, the volume ratio of the precursor solution to the polymer solution is 1:2.5-5. Optionally, in step S3, the annealing conditions include: in an air environment, the annealing temperature is 80-120° C., and the annealing time is 5-30 min. Optionally, when the polymer in the polymer solution used in step S3 is at least one of polyacrylonitrile (PAN) and polyvinylidene chloride (PVDC), the process of obtaining the coating carrier in step S3 adopts the step-by-step coating.
[0013] Optionally, in step S3, the coating conditions in the one-time coating or the step-by-step coating independently include: spin coating at 2000-3000 rpm.
[0014] In this application, the use of high molecular weight polymers to coat quantum dots can not only make the quantum dots more stable, but also allow the material to grow in a confined area through the confinement effect of the polymer, and the quantum dots are more uniform in size. This solves the problem that the ligand-assisted reprecipitation method (anti-solvent method) is difficult to prepare copper-based perovskite quantum dots. The copper-based perovskites prepared by the anti-solvent method are generally large in size and difficult to reach the nanoscale. The hot injection method cannot prepare quantum dots in an air environment. During the spin coating process, if PAN and PVDC are directly mixed with the perovskite precursor and spin-coated, the luminescence uniformity of the obtained film is very poor. However, if a layer of polymer is spin-coated first, and then the perovskite precursor is spin-coated once or twice, and annealed uniformly, a light-emitting film of excellent quality can be obtained through the dissolution-coating process.
[0015] According to the second aspect of the present application, a polymer-coated non-toxic and stable perovskite quantum dot film obtained by the preparation method is provided, wherein the perovskite quantum dots are selected from at least one of CsCu2I3, CsCu2I3, CsCu2I3, Cs3Cu2I5, Cs3Cu2I5, Cs3Cu2I5, and Cs3Cu2Cl5.
[0016] The beneficial effects of this application include: (1) The polymer-coated non-toxic stable perovskite quantum dot film and its preparation method provided in this application prepares pure inorganic metal halide perovskite quantum dots (CsCu2I3, Cs3Cu2I5, Cs3Cu2Cl5) in an air environment by spin coating annealing method involving polymer (PMMA, PAN, PVDC). Compared with the prior art, this application proposes for the first time to use polymer to coat copper-based perovskite quantum dots to achieve confined growth, and to use spin coating annealing method in an air environment to prepare stable pure inorganic metal halide perovskite quantum dots (CsCu2I3, Cs3Cu2I5, Cs3Cu2Cl5).
[0017] (2) This application explores the coating effect of three different polymers: polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), and polyvinylidene chloride (PVDC) on perovskite quantum dots. For different polymers, a step-by-step spin coating method is proposed to ensure the uniformity of luminescence after film formation. At the same time, the high molecular polymer coating can effectively isolate water and oxygen and improve the stability of the material.
[0018] (3) When synthesizing quantum dots in an air environment, it is necessary to consider the effect of oxygen on different materials. This application adopts a strategy that combines independent dissolution with low-speed stirring to control oxygen from entering the precursor solution during the dissolution process to ensure that the material is not oxidized. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a real shot of the Cs3Cu2I5 clarified precursor of this application; Figure 2 This is a real shot of the oxidized Cs3Cu2I5 precursor of this application; Figure 3 Actual photos of Cs3Cu2I5@PMMA film, Cs3Cu2I5@PAN film, and Cs3Cu2I5@PVDC film under fluorescent light and ultraviolet light in this application; Figure 4 Actual photos of fluorescent lamps and UV lamps for CsCu2I3@PMMA film, CsCu2I3@PAN film, and CsCu2I3@PVDC film in this application; Figure 5 This is the transmission electron microscope (TEM) image of the Cs3Cu2I5@PVDC film of this application, with a scale of 50nm. DETAILED DESCRIPTION
[0020] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0021] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0022] Unless otherwise specified, conventional methods were used for testing and instrument settings were those recommended by the manufacturer.
[0023] According to one embodiment of the present application, a method for preparing a polymer-coated non-toxic and stable perovskite quantum dot film comprises the following steps: (1) Preparation of perovskite quantum dot precursor solution Using the preparation steps shown in ① to ③, the precursor solutions of CsCu2I3, Cs3Cu2I5 and Cs3Cu2Cl5 are ready for use: ① From the chemical equation CsI + 2CuI = CsCu2I3, it can be known that CsI and CuI are weighed in the same vial according to the molar ratio of 1:2, DMSO is added to dissolve, and magnetic stirring is performed. After continuous optimization, this application has explored the optimal dissolution dosage: 0.6495g CsI and 0.9525g CuI are dissolved in 2ml DMSO. Considering that CsI and CuI are easily soluble, and the liquid level of 2ml solvent is too low, oxygen can easily enter the precursor during stirring. After doubling the dosage in proportion, use a magnetic stirring at a low speed (with no bubbles generated during the stirring process as the standard), stir for 3 minutes to obtain a clear and transparent CsCu2I3 precursor solution.
[0024] ②According to the chemical equation 3CsI + 2CuI = Cs3Cu2I5, and considering the elimination of the formation of CsCu2I3 phase, the optimal dosage is achieved by dosing at a molar ratio of 2:1. The optimal dissolved dosage is: 0.7795g CsI and 0.2855g CuI dissolved in 2ml DMSO. The dosage is appropriately multiplied according to the ratio, and the magnetic stirrer is still used for 3 minutes at a low speed to obtain a clear and transparent Cs3Cu2I5 precursor solution.
[0025] ③According to the chemical equation 3CsCl + 2CuCl = Cs3Cu2Cl5, considering that CsCl is insoluble, in order to avoid the influence of other phases, the drug is administered at a molar ratio of 2:1. First, CsCl is dissolved in DMSO and stirred vigorously until it is completely dissolved (if it is insoluble for a long time, the residual particles can be filtered out), and then CuCl is added to avoid the oxidation of CuCl caused by the long-term dissolution of CsCl. The optimal dissolution dosage is: 0.5050g CsCl and 0.1485g CuCl dissolved in 7.5ml DMSO. Note that after adding CuCl, stir at a low speed until a clear solution is obtained, that is, a clear and transparent Cs3Cu2Cl5 precursor solution is obtained.
[0026] During the preparation of the perovskite quantum dot precursor solution, if CuCl is oxidized, the color of the precursor will become darker, and after being left for a long time, it will completely turn black and become ineffective. Although the darker precursor can also be used to prepare quantum dots, its XRD spectrum peak intensity is weak and the crystallinity is poor. The oxidation of the precursor should be avoided as much as possible. Therefore, when the quantum dot raw material is dissolved in DMSO, it is stirred at a low speed to avoid bubbles from entering the precursor solution, thereby preventing oxidation and discoloration. When the solution becomes clear and transparent, the quantum dot raw material has been dissolved.
[0027] (2) Preparation of polymer solution Dissolve three polymers, methyl methacrylate (PMMA), polyacrylonitrile (PAN), and polyvinylidene chloride (PVDC), in DMSO to obtain PMMA solution, PAN solution, and PVDC solution for standby use; Among them, the concentration of PMMA solution is 1g / 5ml, the concentration of PAN solution is 0.1-0.2g / ml, and the concentration of PVDC solution is 1g / 5ml.
[0028] In the preparation process of high molecular polymer solution, PAN is used in a smaller amount because it is too viscous; PMMA and PAN are completely dissolved after being added to DMSO and stirred for one day; PVDC is difficult to dissolve, so it is centrifuged after one day of dissolution and the supernatant is used.
[0029] (3) Perovskite quantum dots@polymer film The perovskite quantum dot precursor solution and the high molecular polymer solution in step (1) and step (2) are used to prepare CsCu2I3@PMMA, CsCu2I3@PAN, CsCu2I3@PVDC, Cs3Cu2I5@PMMA, Cs3Cu2I5@PAN, Cs3Cu2I5@PVDC, and Cs3Cu2Cl5@PMMA films, respectively. Steps ① to ⑦ are shown as follows: ① CsCu2I3@PMMA: Take 2 ml of the CsCu2I3 precursor solution in step (1) and add it to 5 mL of the PMMA solution with a concentration of 1 g / 5 ml in step (2). After stirring and mixing evenly, spin coat at 2500 rpm (a=800 rpm / s) to form a film, and quickly place it in an oven for annealing at 80°C for 10 min.
[0030] ②Cs3Cu2I5@PMMA: Take 2 ml of the Cs3Cu2I5 precursor solution in step (1) and add it to 5 mL of the PMMA solution with a concentration of 1 g / 5 ml in step (2). After stirring and mixing evenly, spin coat at 2500 rpm (a=800 rpm / s) to form a film, and quickly place it in an oven for annealing at 80°C for 10 min.
[0031] ③Cs3Cu2I5@PAN: First, take 0.75mL of PAN with a concentration of 0.2g / 5ml in step (2) and spin-coat it at 2500rpm (a=800rmp / s) to form a film. Then, directly add 0.5mL of the Cs3Cu2I5 precursor solution in step (1) and spin-coat it again at 2500rpm (a=800rmp / s). At this time, the DMSO in the precursor will dissolve the PAN and allow the precursor to enter the PAN film. The film is quickly placed in an oven for annealing at 80°C for 10 minutes to achieve the coating effect.
[0032] ④CsCu2I3@PAN: First, take 0.75mL of PAN with a concentration of 0.1g / 5ml in step (2) and spin-coat it at 2500rpm (a=800rmp / s) to form a film. Then, directly add 0.5mL of the CsCu2I3 precursor solution in step (1) and spin-coat it twice at 2500rpm (a=800rmp / s). Then, add the precursor and spin-coat it three times at 2500rpm (a=800rmp / s) to make the luminescence most uniform. Then, quickly place it in an oven and anneal it at 80℃ for 10min.
[0033] ⑤CsCu2I3@PVDC: 0.75mL of 1g / 5ml PVDC in step (2) is spin-coated at 2500rpm (a=800rmp / s) to form a film, then 0.5mL of the CsCu2I3 precursor solution in step (1) is directly added and spin-coated for a second time at 2500rpm (a=800rmp / s) (the precursor can be added and spin-coated for a third time depending on the situation), and then quickly placed in an oven for annealing at 80°C for 10min.
[0034] ⑥Cs3Cu2I5@PVDC: 0.75mL of 1g / 5ml PVDC in step (2) is spin-coated at 2500rpm (a=800rmp / s) to form a film, then 0.5mL of the Cs3Cu2I5 precursor solution in step (1) is directly added and spin-coated for a second time at 2500rpm (a=800rmp / s) (the precursor can be added and spin-coated three times depending on the situation), and then quickly placed in an oven for annealing at 80°C for 10min.
[0035] ⑦Cs3Cu2Cl5@PMMA: Take 2 ml of the Cs3Cu2Cl5 precursor solution in step (1) and add it into 5 mL of the PMMA solution with a concentration of 1 g / 5 ml in step (2). After stirring and mixing evenly, spin coat at 2500 rpm (a=800 rpm / s) to form a film, and quickly place it in an oven to anneal at 80°C for 10 min.
[0036] The applicant found during the preparation process that if PAN and PVDC were directly mixed with the precursor and spin-coated, the film would not be uniform, so a step-by-step spin-coating method was adopted. After trial, the method of first spin-coating the polymer (without annealing) and then spin-coating the precursor could achieve the best effect. CsCu2I3 and Cs3Cu2I5 are easy to agglomerate with PMMA, and the remaining liquid except the agglomerates was spin-coated, which did not affect the experimental results.
[0037] Test Case Taking the preparation of Cs3Cu2I5@PVDC as an example, the Cs3Cu2I5 precursor solution obtained in step (1) is shown in the figure. Figure 1 As shown. If CuCl is oxidized, the color of the precursor will become darker ( Figure 2 ) will affect the crystallinity of quantum dots; the transmission electron microscopy (TEM) image of the Cs3Cu2I5@PVDC film prepared in step (3) is shown in Figure 5 shown.
[0038] Taking Cs3Cu2I5@PMMA, Cs3Cu2I5@PAN, Cs3Cu2I5@PVDC, CsCu2I3@PMMA, CsCu2I3@PAN, and CsCu2I3@PVDC as examples, thin films were prepared on 2cm×2cm glass sheets respectively. After spin coating, they were quickly placed in a preheated 80℃ oven for annealing for 10 minutes, and the quantum dot film was prepared. In this process, the amount required for spin coating a 2cm×2cm glass sheet is: if it is a second spin coating, 0.5ml of precursor solution and 0.75ml of polymer solution are required, and if it is a single spin coating, 0.75ml of a mixed solution of precursor and polymer is required.
[0039] The test results of the prepared films are as follows: The actual pictures of Cs3Cu2I5@PMMA, Cs3Cu2I5@PAN, and Cs3Cu2I5@PVDC films under fluorescent light and ultraviolet light are as follows: Figure 3 As shown in the figure, the actual pictures of CsCu2I3@PMMA, CsCu2I3@PAN and CsCu2I3@PVDC under fluorescent light and ultraviolet light are as follows: Figure 4 shown.
[0040] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing a polymer-coated non-toxic and stable perovskite quantum dot film, characterized in that: The steps include: S1. Obtain a raw material containing cuprous halide and cesium halide, add it into DMSO, and stir until it becomes clear and transparent to obtain a precursor solution; S2, obtaining a polymer solution containing a high molecular weight polymer and DMSO; S3, in an air environment, coating the precursor solution and the polymer solution on a carrier once or step by step to obtain a coated carrier, annealing the coated carrier to obtain a non-toxic and stable perovskite quantum dot film coated with the polymer; Wherein, the one-time coating includes mixing the precursor solution and the polymer solution and coating the mixture on the carrier to form a film; The step-by-step coating includes coating the polymer solution on a carrier to form a polymer film, and coating a precursor solution on the polymer film to form a film.
2. The preparation method according to claim 1, characterized in that: In step S1, the cuprous halide is selected from at least one of CuI and CuCl.
3. The preparation method according to claim 1, characterized in that: In step S1, the cesium halide is selected from at least one of CsI and CsCl.
4. The preparation method according to claim 1, characterized in that: In step S1, the usage ratio of cuprous halide, cesium halide and DMSO is: 1 g: 0.55-0.75 g: 2-4 mL.
5. The preparation method according to claim 1, characterized in that: In step S2, the high molecular polymer is selected from at least one of methyl methacrylate, polyacrylonitrile and polyvinylidene chloride.
6. The preparation method according to claim 1, characterized in that: In step S2, the usage ratio of the high molecular weight polymer to DMSO is 1 g: 4-10 mL.
7. The preparation method according to claim 1, characterized in that: In step S3, during the process of mixing the precursor solution and the polymer solution, the volume ratio of the precursor solution to the polymer solution is 1:2.5-5.
8. The preparation method according to claim 1, characterized in that: In step S3, the annealing conditions include: in an air environment, the annealing temperature is 80-120° C., and the annealing time is 5-30 min.
9. The preparation method according to claim 1, characterized in that: When the polymer in the polymer solution used in step S3 is at least one of polyacrylonitrile and polyvinylidene chloride, the process of obtaining the coating carrier in step S3 adopts the step-by-step coating.
10. The polymer-coated non-toxic and stable perovskite quantum dot film obtained by the preparation method according to any one of claims 1 to 9, characterized in that: The perovskite quantum dots are selected from at least one of CsCu2I3, CsCu2I3, CsCu2I3, Cs3Cu2I5, Cs3Cu2I5, Cs3Cu2I5, and Cs3Cu2Cl5.